Correlation of serum insulin like growth factor-I with retinopathy in Malaysian pregnant diabetics - Adzura, Salam; Muhaya, M; Zaleha, A. M.; Sharifa Ezat, W.P (Zhonghua Yixuehui Xian Fenhui, 2011)
AIM: To study the association of serum insulin-like growth factor-I (IGF-I) with diabetic retinopathy. ·METHODS: Serum IGF-1 levels were measured in 25 pregnant diabetic patients and 25 pregnant non-diabetic patients who were matched for age, ethnicity, parity and period of gestation. Fundus examination was performed in both groups at 28, 32 and 36 weeks of gestation. ·RESULTS: The serum IGF-I level was significantly elevated in pregnant diabetics compared to pregnant non-diabetics (366± 199滋g/L 184± 89滋g/L, ( =0.0001) at 24 weeks, 535± 251滋g/L 356± 89滋g/L, ( =0.007) at 32 weeks and 404± 166滋g/L 264± 113滋g/L, ( =0.003) at 36 weeks of gestation). The pregnant diabetics with established diabetes had significantly higher IGF-1 level than gestational diabetes at 28, 32 and 36 weeks of gestation. The serum IGF-I level in pregnant diabetics with retinopathy was significantly higher than in those without retinopathy at all periods of gestation.